Effect of Growth Mindset on School Engagement and Psychological Well-Being of Chinese Primary and Middle School Students: The Mediating Role of Resilience - Zeng, Guang; Hou, Hanchao; Peng, Kaiping (Frontiers in Psychology, 2016)
The objective of positive education is not only to improve students’ well-being but also their academic performance. As an important concept in positive education, growth mindset refers to core assumptions about the malleability of a person’s intellectual abilities. The present study investigates the relation of growth mindsets to psychological well-being and school engagement. The study also explores the mediating function of resilience in this relation. We recruited a total of 1260 (658 males and 602 females) Chinese students from five diversified primary and middle schools. Results from the structural equation model (SEM) show that the development of high levels of growth mindsets in students predicts higher psychological well-being and school engagement through the enhancement of resilience. The current study contributes to our understanding towards the potential mechanisms of how positive education (e.g. altering the mindset of students) can impact psychological well-being and school engagement.